HEMATOLOGICAL AND SEROLOGICAL EVIDENCE OF EHRLICHIA SPP IN OWNERS OF DOMESTIC CANINES WITH HISTORY OF EHRLICHIOSIS IN LIMA - Barrios A., Luis (2013)
The aim of this study was determine the frequency of seropositivity to a Ehrlichia canis in human subjects by indirect inmunofluorescent test (IFI), hematological changes and its association with risk factors such as age, gender, level of contact with dogs, and tick exposure. Ninety-one samples were collected from patients without reference to gender, age and socioeconomic status, but whose dogs had history of ehrlichiosis within six months to the sampling. The study was conducted between February and May 2010. Hematology results revealed absence of positive cases and 15.4% of suspected cases (presence of inclusion bodies in mononuclear cells and absence of thrombocytopenia). Frequency of IFI seropositives was 14.3%. No statistical difference was found due to the effect of the variables under evaluation. The results confirm exposure to E. canis in dog owners with previous record of ehrlichiosis in Metropolitan Lima.